(untitled) (Journal of EAHIL, 2024)
Competency frameworks are essential for identifying job-specific skills, highlighting training needs, and enabling skill development. Therefore, the Dutch Association for Biomedical Information Professionals (KNVI-BMI) created a framework for health information specialists. Competencies were defined as the integration of knowledge, skills, and attributes required for effective job performance. The framework was developed through literature review, job postings analyses, and consensus meetings to select and categorize relevant competencies. An expert opinion survey validated the preliminary framework. The final framework includes nine domains: 1) healthcare environment, 2) information and literature services, 3) management of information resources, 4) information systems, technology, and applications, 5) didactics and teaching of information literacy, 6) research methodology, 7) research data management, 8) leadership and management, and 9) professionalism.